The utility of fecal calprotectin in predicting the need for escalation of therapy in inflammatory bowel disease. (3rd August 2017) - Kwapisz, Lukasz; Gregor, Jamie; Chande, Nilesh; Yan, Brian; Ponich, Terry; Mosli, Mahmoud
Abstract: Background and aims: Fecal calprotectin is an important biomarker used in the evaluation of inflammatory bowel disease. It has proven to be an effective tool in initial screening as well monitoring response to therapy. The aim of this study is to examine the utility of fecal calprotectin both as a predictor for the escalation of therapy in established inflammatory bowel disease and as a predictor of de novo diagnosis. Methods: Patients with signs and symptoms concerning for inflammatory bowel disease presenting to outpatient clinics were recruited to provide fecal calprotectin stool samples prior to endoscopic evaluation. Patients were followed up for at least one year and monitored clinically for any change in symptomatology, escalation of therapy or development of IBD, confirmed endoscopically. Results: A total of 126 patients, of whom 72 were known to have underlying inflammatory bowel disease, were included in the final analysis. Among the patients with elevated fecal calprotectin levels and known inflammatory bowel disease, 66% (33/50) went on to have escalation of therapy within 12 months compared to 18% (4/22) if the fecal calprotectin levels were in the normal range ( p  < .0001). For the remaining patients who at baseline did not have inflammatory bowel disease and a normal endoscopic evaluation, elevated fecal calprotectin resulted in no cases (0/17) of a new diagnosis in the next 12 months. Conclusions: Fecal calprotectin is a useful test for predicting escalation of therapy in established inflammatory bowel disease.